Anti-melanogenesis and anti-inflammatory actvities of selected medicinal and culinary mushrooms / Hazwani Mat Saad - Hazwani , Mat Saad (2017)
Ten medicinal and culinary mushrooms which commonly available in Malaysia market, namely Agaricus bisporus (white and brown varieties), Flammulina velutipes, Ganoderma lucidum, Grifola frondosa, Hypsizygus marmoreus, Lentinula edodes, Pleurotus eryngii, Pleurotus floridanus and Pleurotus pulmonarius were investigated for their anti-melanogenesis and anti-inflammatory activity in attempt to study their potentials to be used in cosmeceuticals. The mushrooms were extracted with hot water and freeze-dried prior for testing. The anti-melanogenesis activity of mushroom extracts were determined by cell-free mushroom tyrosinase assay, followed by cell viability assay, measurement of intracellular melanin content and cellular tyrosinase assay using B16F10 murine melanoma cells. Whilst, the anti-inflammatory activity of the mushroom extracts was tested by measuring the level of nitric oxide (NO), tumor necrosis factor alpha (TNF-α) and interleukin (IL)-10 excreted by RAW 264.7 murine macrophage cells. Out of the ten extracts, A. bisporus (brown), P. floridanus and P. pulmonarius effectively reduced the intracellular melanin content and cellular tyrosinase activity in B16F10 cells. A. bisporus (brown) was the best extract in reducing intracellular melanin content to 57.05 ± 3.90% at concentration of log 3.0 with no toxicity effects on B16F10 cells. This extract also reduced cellular tyrosinase activity to 17.93 ± 2.65%, which performed better than positive control, kojic acid (33.81 ± 7.41%). In parallel, A. bisporus (brown) extract has appreciable antiinflammatory activity by reducing the NO and TNF-α level (66.82 ± 2.81% and 73.67 ± 2.97%, respectively) at highest concentration tested. A reduction of NO level was also being observed for P. floridanus and P. pulmonarius extracts at similar concentrations. Based on the effectiveness of single extract to inhibit melanogenesis and inflammatory response, three combination mushroom extracts comprise of G. lucidum with P. floridanus or P. pulmonarius at 1:1 ratio was formulated and the synergistic effect of these combined extracts was evaluated. The results revealed that combined mushroom extracts did not have synergistic effect in these biological activities. In summary, single extract was more active than the combine extracts. Our findings also showed that A. bisporus (brown) extract has potential to be used as natural ingredients in cosmeceutical products.